THE EFFORTS TO INCREASE THE ROLE OF BHABINKAMTIBMAS SATBINMAS PEMALANG POLICE THROUGH BIMLUH TO PREVENT GAMBLING IN THE FRAMEWORK OF HARKAMTIBMAS - Jodi Utama (Police Studies Review, 2022)
The National Police is a state institution whose function is to maintain internal security. With the many phenomena in society, coupled with the COVID-19 pandemic, which adds to the number of public order disturbances that occur, including gambling problems. To overcome this, there needs to be a preemptive effort from the Police, namely through Bhabinkamtibmas with various kinds of activities such as Bimluh. In this final project, the problem includes how the role of Bhabinkamtibmas Satbinmas Pemalang Police through Bimluh to prevent gambling in the context of Harkamtibmas and what are the efforts of Bhabinkamtibmas Satbinmas Pemalang Police through Bimluh to prevent gambling in the context of Harkamtibmas. As a Research Instrument, the author uses management theory, and the concepts of Bhabinkamtibmas, Bimluh Kamtibmas, and Gambling. This thesis uses a qualitative approach. The type of research is field research, while the data collection technique is through interviews, observations, and document studies. For the data analysis technique, the writer uses data reduction, data presentation, and drawing conclusions. In this paper it is concluded that the implementation of Bimluh activities by Bhabinkamtibmas is still not optimal, referring to the concepts and theories used, and several efforts from Bhabinkamtibmas such as Dai Kamtibmas and Pokdar Masyarakat.